PENGARUH MODEL PEMBELAJARAN PROJECT CITIZEN BERBASIS TPACK TERHADAP PENGUATAN KARAKTER PEDULI LINGKUNGAN SISWA DI SMK NEGERI 1 KUTACANE (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Abstract This study aims to assess the impact of the TPACK-based Project Citizen learning model on improving students' environmental awareness at SMK Negeri 1 Kutacane. The research findings showed that the data were normally distributed (Sig. > 0.05) and had a uniform variance (Sig. 0.530 > 0.05), thus meeting the test criteria. Descriptive analysis findings showed that the experimental class obtained an average score of 88.09, far exceeding the control class which only achieved 53.94. Based on hypothesis testing using Project Citizen, TPACK, and Environmental Awareness, the Independent Sample T-Test obtained a Sig. (2-tailed) value of 0.000 < 0.05, which indicates that H0 is rejected and Ha is accepted. Therefore, it can be concluded that the implementation of the TPACK-based Project Citizen learning model has a significant influence on strengthening students' environmental awareness.